Analisis Pemasaran Maggot BSF (Black Soldier Fly) Desa Bojo - Ahmad; Nur, Irawati; Putra, Ririn Ade (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
This study aims to analyze the marketing system of maggot bsf in Bojo Village. Based on the results of observations and interviews in Bojo Village, the main problem was found, namely household waste. The garbage was thrown out of place, the garbage was found scattered on the beach and close to residential areas. The waste that is wasted includes organic waste from household waste. Organic waste can cause environmental problems such as air and soil pollution and cause various negative impacts on public health. A solution that can be done by village communities is maggot cultivation from Black Soldier Fly (BSF) flies, as an effective and easy way to manage organic waste. By cultivating maggot for organic waste, we can create a high-value resource that can have a positive impact on the environment and the economy of the village community. Maggot cultivation aims to decompose organic matter left over from household food consumption. Able to digest organic waste quickly so that it helps reduce the volume of organic waste. In addition, maggots are also able to prevent uncontrolled accumulation of waste. In fact, casgot which is the result of the decomposition of waste carried out by maggot can produce high-quality organic fertilizer that can increase soil fertility. Maggot has a high nutrient content that helps local agriculture. Maggot cultivation can also be a new business opportunity for village communities because it can be sold as animal feed. It has an impact on increasing the income of the local community.